Pengaruh Lingkungan Kerja, Disiplin Kerja, Dan Kompensasi Kerja Terhadap Kinerja Karyawan Di PT. Bakrie Pipe Industries - Juliarahmawati, Vira; Silalahi, Edward Efendi; Hasanuddin Hasanuddin (CV. KAMPUS AKADEMIK PUBLISING, 2025)
In this era of globalization and intense industrial competition, companies are required to improve their efficiency and effectiveness in order to maintain their competitiveness. This study aims to analyze the influence of work environment, work discipline, and work compensation on employee performance at PT. Bakrie Pipe Industries. The background of this study is based on the phenomenon of declining employee performance identified through the results of a pre-survey, where the majority expressed dissatisfaction with working conditions, the implementation of discipline, and the compensation system. This study uses a quantitative method, with data collection conducted through a questionnaire administered to 84 employees of PT. Bakrie Pipe Industries. The data analysis technique used was Partial Least Square (PLS) with the assistance of SmartPLS 4.0 software. The results of the study indicate that the work environment has a positive and significant effect on employee performance, work discipline does not have a significant effect on employee performance, and compensation has a positive and significant effect on employee performance.